The courtship choreography of homologous chromosomes: timing and mechanisms of DSB-independent pairing - Solé, Mireia; Pascual, Álvaro; Anton, Ester; Blanco, Joan; Sarrate, Zaida (Frontiers in Cell and Developmental Biology, 2023)
Meiosis involves deep changes in the spatial organisation and interactions of chromosomes enabling the two primary functions of this process: increasing genetic diversity and reducing ploidy level. These two functions are ensured by crucial events such as homologous chromosomal pairing, synapsis, recombination and segregation. In most sexually reproducing eukaryotes, homologous chromosome pairing depends on a set of mechanisms, some of them associated with the repair of DNA double-strand breaks (DSBs) induced at the onset of prophase I, and others that operate before DSBs formation. In this article, we will review various strategies utilised by model organisms for DSB-independent pairing. Specifically, we will focus on mechanisms such as chromosome clustering, nuclear and chromosome movements, as well as the involvement of specific proteins, non-coding RNA, and DNA sequences.